Case Report: CAR-T therapy for primary cerebellar ALK-negative anaplastic large cell lymphoma - Zou, Zhongqing; Lai, Sihan; Yi, Hai; Zhang, Qian; Yao, Hao; Yang, Hui; Zhang, Ling; Chang, Alex H.; Su, Yi; Rao, Jin (Frontiers in Immunology, 2025)
Primary central nervous system (CNS) T-cell lymphomas, such as anaplastic large-cell lymphoma (ALCL) with anaplastic lymphoma kinase (ALK) negativity, are relatively rare and aggressive. Despite the administration of high-dose methotrexate (HD-MTX) therapy, the prognosis remains pessimistic. We reported a 21-year-old male patient initially presented with headache and fever. Following surgical intervention, the pathological examination confirmed the diagnosis of ALK-negative ALCL, and the patient was in a critical postoperative condition, evidenced by a Glasgow Coma Scale (GCS) score ranging from 5 to 9. After undergoing chemotherapy with HD-MTX, CD30 and CD7-targeted chimeric antigen receptor T (CAR-T) cells were sequentially infused. The initial infusion dosage was 0.5×106 cells per kilogram (kg) of body weight, which was subsequently adjusted to 1×106 cells per kg. During this therapeutic process, grade 2 cytokine release syndrome (CRS) occurred. However, the CAR-T cells exhibited robust expansion in the peripheral blood, and the patient’s level of consciousness improved significantly, as indicated by an increase in the GCS score to a range of 12 to 15. A 15-month follow-up assessment revealed no evidence of tumor recurrence, and the patient was able to ambulate with the assistance of rehabilitation equipment. This case represents the first globally successful instance of treating ALK-negative primary central nervous system anaplastic large-cell lymphoma (PCNSALCL) with CAR-T therapy. It validates the feasibility and safety of the sequential CD30/CD7 CAR-T therapy for rare CNS T-cell lymphomas, offering a novel treatment strategy for these conditions. Nevertheless, further long-term follow-up and evaluation are essential to determine its sustained efficacy and immunological implications.